Assessing Performance Outcomes in Marketing - Katsikeas, Constantine S.; Morgan, Neil A.; Leonidou, Leonidas C.; Hult, G. Tomas M. (Journal of Marketing, 2016)
Research in marketing has increasingly focused on building knowledge about how firms’ marketing contributes to performance outcomes. A key precursor to accurately diagnosing the value firms’ marketing creates is conceptualizing and operationalizing appropriate ways to assess performance outcomes. Yet, to date, there has been little conceptual development and no systematic examination of how researchers in marketing should conceptualize and measure the performance outcomes associated with firms’ marketing. The authors develop a theory-based performance evaluation framework and examine the assessment of such performance outcomes in 998 empirical studies published in the top 15 marketing journals from 1981 through 2014. The results reveal a large number of different performance outcome measures used in prior empirical research that may be only weakly related to one another, making it difficult to synthesize findings across studies. In addition, the authors identify significant problems in how performance outcomes in marketing are commonly conceptualized and operationalized. They also reveal several theoretically and managerially important performance areas in which empirical knowledge of marketing's impact is limited or absent. Finally, they examine the implications of the results, provide actionable guidelines for researchers, and suggest a road map for systematically improving research practice in the future.